Pengaruh Iklan dan Citra Merek terhadap Keputusan Pembelian Sabun Mandi Lifebuoy di Kota Semarang dengan Minat Beli sebagai Variabel Intervening - Munaya Ayu Prasasti; Mochamad Fadjar Darmaputra; Ratih Hesty Utami Puspitasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The personal care product industry, particularly bath soap, is becoming increasingly competitive as public awareness of health and hygiene grows. Lifebuoy is a long-trusted bath soap brand, but according to data from the Top Brand Index 2021–2024, Lifebuoy is experiencing a significant downward trend. This situation indicates a problem in consumer purchasing decisions, making it crucial to examine the factors influencing it. This study aims to analyze the influence of advertising and brand image on purchasing decisions for Lifebuoy bath soap in Semarang City, with purchase intention as an intervening variable. This study used a quantitative approach with explanatory research. The population in this study was all Lifebuoy bath soap users in Semarang City. The sample was determined using a non-probability sampling method using the Lemeshow formula, resulting in 96 respondents. Data analysis techniques used Descriptive Statistical Analysis, Measurement Model Evaluation (Outer Model), and Structural Model Evaluation (Inner Model) using the SmartPLS 0.4 application. The results of the study indicate that advertising has a direct influence on purchasing decisions, brand image has a positive and significant influence on purchasing decisions, advertising does not have a significant direct influence on purchase intention, brand image has a positive and significant influence on purchase intention, purchase intention has a positive and significant influence on purchase decisions, purchase intention mediates the relationship between advertising and purchase decisions, and purchase intention mediates the relationship between brand image and purchase decisions.